1996
DOI: 10.3109/01480549609002198
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Rats Fed Loline and Ergot Alkaloids from Endophyte-Infected Tall Fescue

Abstract: Sixty-three male sprague Dawley rats were randomly assigned to dietary treatments containing 1) N-formylloline alkaloid (NFL), 2) N-acetylloline alkaloid (NAL), 3) NFL + NAL, 4) NFL + a mixture of ergot alkaloids, 5) NAL + a mixture of ergot alkaloids, 6) NFL + NAL + a mixture of ergot alkaloids, 7) a mixture of ergot alkaloids, 8) endophyte-free tall fescue seed (EFTF), and 9) endophyte-infected tall fescue (EITF) seed (negative control). All diets were prepared by mixing the prepared treatments and Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, an unusual ether bridge between C-2 and C-7, a completely saturated pyrrolizidine ring, and an amino group at C-1 are structural features distinguishing the lolines from the necines (Bush et al, 1993;Schardl et al, 2007). Unlike the necines, which have potent anti-mammalian activities (Hartmann and Witte, 1995;Pelser et al, 2005), notably strong hepatotoxicity and carcinogenicity (Fu et al, 2004), lolines lack significant mammalian toxicity (Jackson et al, 1996). The potent insecticidal activity of the lolines and the lack of anti-mammalian activity have generated interest in these compounds as plant protectants.…”
Section: Introductionmentioning
confidence: 96%
“…However, an unusual ether bridge between C-2 and C-7, a completely saturated pyrrolizidine ring, and an amino group at C-1 are structural features distinguishing the lolines from the necines (Bush et al, 1993;Schardl et al, 2007). Unlike the necines, which have potent anti-mammalian activities (Hartmann and Witte, 1995;Pelser et al, 2005), notably strong hepatotoxicity and carcinogenicity (Fu et al, 2004), lolines lack significant mammalian toxicity (Jackson et al, 1996). The potent insecticidal activity of the lolines and the lack of anti-mammalian activity have generated interest in these compounds as plant protectants.…”
Section: Introductionmentioning
confidence: 96%
“…Some studies report negative effects, such as decreases in population density (Coley et al, 1995), increased toxicity-induced mortality (Conover, 1998) and suppression of reproduction and growth (Jackson et al, 1996; Durham and Tannenbaum, 1998; Fortier et al, 2000; Conover, 2003), while others have found no effects at all (Barger and Tannenbaum, 1998; Saari et al, 2010). Thus, the effects of endophytic fungi on herbivores may be dose-dependent and may vary between grass, fungi and herbivore species.…”
Section: Introductionmentioning
confidence: 99%
“…7). The ecological significance of lolines has been linked to their anti-invertebrate and feeding deterrent activities, while they seem to be weakly or nontoxic to mammalian herbivores [53,54]. Yet the production of lolines by the endophytic fungi in plant is likely to be substantial, approaching up to 2% of the plant dry mass [51b].…”
Section: Studies In Natural Products Chemistrymentioning
confidence: 99%